Economic growth and equity in anticipation of climate policy - Alena Miftakhova; Clément Renoir (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
We study the role of the anticipation of climate policies on equity and economic growth in a numerical model of general equilibrium. The presence of the anticipation period allows the agents to adjust their choices before policy implementation. This period might change the equilibrium dynamics. It might also impact the redistribution of wealth in the economy. We choose the Swiss economy to exemplify and analyze these effects. The supply-side of the economy adjusts by redirecting the investments to "cleaner" sectors with a lower tax burden and higher profitability. On the demand side, welfare impacts by households vary according to their principal source of income. Households that have a high share of their income from capital rents benefit more from the policy's announcement than others do. We find that, for the most stringent climate policies, the effect of anticipation is strongly positive but also regressive.
Keywords: C63; E62; O44; Q43; Q48; 330; Climate policy; Environmental tax; Economic inequality; Endogenousgrowth; CGE Modelling